Cytoplasmic Ca2+ influx mediates iron- and reactive oxygen species-dependent ferroptotic cell death in rice immunity - Wang, Juan; Choi, Won-Gyu; Nguyen, Nam Khoa; Liu, Dongping; Kim, Su-Hwa; Lim, Dongyeol; Hwang, Byung Kook; Jwa, Nam-Soo (Frontiers in Plant Science, 2024)
Iron-and reactive oxygen species (ROS)-dependent ferroptosis occurs in plant cells. Ca 2+ acts as a conserved key mediator to control plant immune responses. Here, we report a novel role of cytoplasmic Ca 2+ influx in the regulation of ferroptotic cell death in rice immunity. High Ca 2+ influx triggered irondependent ROS accumulation, lipid peroxidation, and subsequent hypersensitive response (HR) cell death in rice (Oryza sativa). During Magnaporthe oryzae infection, 14 different Ca 2+ influx regulators altered Ca 2+ , ROS and Fe 2+ accumulation, glutathione reductase (GR) expression, glutathione (GSH) depletion and lipid peroxidation, leading to ferroptotic cell death in rice. High Ca 2+ levels inhibited the reduction of glutathione disulfide (GSSG) to GSH in vitro. Ca 2+ chelation by ethylene glycol-bis (2aminoethylether)-N, N, N′, N′-tetra-acetic acid (EGTA) suppressed apoplastic Ca 2+ influx in rice leaf sheaths during infection. Blocking apoplastic Ca 2+ influx into the cytoplasm by Ca 2+ chelation effectively suppressed Ca 2+ -mediated iron-dependent ROS accumulation and ferroptotic cell death. By contrast, acibenzolar-S-methyl (ASM), a plant defense activator, significantly enhanced Ca 2+ influx, as well as ROS and iron accumulation to trigger ferroptotic cell death in rice. The cytoplasmic Ca 2+ influx through calcium-permeable cation channels, including the putative resistosomes, could mediate ironand ROS-dependent ferroptotic cell death under reduced GR expression levels in rice immune responses.